On the streets and in the state house : American Indian and Hispanic women and environmental policymaking in New Mexico - Prindeville, Diane-Michele, 1959- (Indigenous peoples and politics., 2004)
This study explores the politics of American Indian and Hispanic women leaders in New Mexico's environmental policymaking arena.